Do Index Insurance Programs Live Up to Their Promises? Aggregating Evidence from Multiple Experiments - Castaing, Pauline (World Bank, Washington, DC, 2022)
Despite limited uptake, index insurance is often seen as one of the most remarkable innovations of the past decades to help smallholder farmers manage risks. This paper uses a Bayesian hierarchical model to aggregate evidence from existing experiments and assess the external validity of their results. The findings show positive but highly heterogeneous responses to index insurance across experiments. Interventions expanding access to index insurance typically boost productive investments by 0.06–0.11 standard deviation on average. However, treatment effects display substantial heterogeneity and there is no evidence that this heterogeneity can be meaningfully explained by basic household characteristics. The existing evidence base thus offers limited insights to predict the impact of index insurance in new settings. The paper concludes that governments and development agencies should remain cautious before investing in the widespread expansion of index insurance.